Bentuk Pertanggungjawaban Pidana Pelaku Judi Sabung Ayam (Tajen) dalam Upacara Adat Tabuh Rah: (Studi kasus di Desa Pemaron Kabupaten Buleleng, Prov. Bali) - Ade Wahyu Permana; Dairani Dairani; Syahrul Ibad (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Tabuh Rah in Bali is part of a Hindu religious ceremony involving animal sacrifice to maintain harmony between nature and human life. In practice, it is often accompanied by tajen (cockfighting) involving monetary or valuable bets, potentially violating Article 303 of the Indonesian Criminal Code concerning gambling. This study examines the regulation of cockfighting as a criminal offense under Article 303 and the criminal liability of perpetrators of tajen within the context of the Tabuh Rah ceremony. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that cockfighting conducted as part of the Tabuh Rah ritual is permissible based on the Batur Agung Inscription (933 Saka) and the Batuan Inscription (944 Saka) without requiring official authorization. However, cockfighting conducted outside the ritual context and involving betting constitutes gambling in violation of the Criminal Code and Law No. 7 of 1974. Perpetrators may be held criminally liable for intentionally committing an unlawful act.